Innovations and challenges: women, language and sexism - Caldas-Coulthard, Carmen Rosa (New York: Routledge, 2020)
"Innovations and Challenges: Women, Language and Sexism brings together an outstanding collection of internationally recognised researchers to recontextualise some of the questions raised by feminist thinkers 40 years ago. The topic of gender and language has evolved tremendously in the last decades and research has contributed in many ways to a heightened awareness of gender-inflected discourse. Many of the issues discussed in the 70s and 80s, however, continue to be a problem as sexism, racism and ageism in discourses in private and institutional contexts have manifested in fresh ways in recent years. In linguistics and discourse-oriented applied research, the question of plain sexism has been side-lined since sexuality and gender identity seem to be the present concerns of the great majority of gender research. By taking linguistically mediated violence as a central topic, this collection's main objective is to explore the different and subtle ways sexism and violence are materialised in discursive practices. In doing so, this book: Takes a multi-stranded investigation into the linguistic and semiotic representations of sexism in societies today from an applied linguistic and semiotic perspective; Combines critical discourse analysis, multimodality, interactional sociolinguistics and corpus methodologies to look at language, visuals and semiotic resources in the context of consumerist culture; Examines the conflicted position of women and the discourses of discrimination that still exists in every strand of modern societies; Contextualises pervasive gender issues and reviewing key gender and language topics that changed the ways we interpret interaction from the early seventies till the present; Focuses on institutional discourses and the questions of how women are excluded or discriminated against in the workplace, the law and educational contexts. This book is essential reading for those studying and researching gender across a wide range of disciplines"--
Language, Discourse and Gender Violence. Women, language, and public discourse: five decades of sexism and scrutiny / Alice F. Freed -- Gender respect gap / Deborah Cameron -- The transgressive, the traditional: sexist discourses of grandmothering and ageing / Carmen Rosa Caldas-Coulthard and Rosamund Moon -- Disco divas and heroic knights: a critical multimodal analysis of gender roles in "Create the World" LEGO cards / Jai Mackenzie, Laura Coffey-Glover, Sophie Payne, Mark McGlashan -- Sexual harassment as reported by the Brazilian press: ambivalent and contradictory framings / Branca Telles Ribeiro and Liliana Cabral Bastos -- Sexism and Institutional Discourses. 'Until I got a man in he wouldn't listen': evidence for the gender order in New Zealand workplaces / Janet Holme -- Sexism and mediatized recontextualizations: the case of a battered woman who killed / Sibley Slinkard and Susan Ehrlich -- The Discourse of (re)exploitation: female victims in the legal system / Nicci Macleod -- Language-based discrimination in schools: intersections of gender and sexuality / Helen Sauntson.
Includes index.
Description based on print version record and CIP data provided by publisher.
Keywords: Sexism in language; Language and languages -- Sex differences; Language and sex; Women -- Language